IMPLEMENTASI PROGRAM TAHFID AL QUR’AN DALAM MEMBENTUK KEDISIPLINAN SANTRI DI PONDOK PESANTREN PUTRI AL-WASHOYA KERTOREJO JOMBANG - Zulva Rojauna; Rofiatul Hosna (CV. ALIM'SPUBLISHING, 2024)
This study examines the implementation of the tahfid Al-Qur'an program in forming student discipline at the Al-Washoya Islamic Boarding School Kertorejo Jombang. Data was collected through observation, interviews and documentation. The research findings are that the tahfid Al-Qur'an program can provide character education values ​​to al-washoya students. The character that is the main objective of implementing the tahfid Al-Qur'an program is to form student discipline. Several supporting factors in forming santri discipline through the tahfid Al-Qur'an program are takhasus books, santri intelligence, the high interest of santri, attention from ustadzahs, and giving reminders. The inhibiting factors are that some students are not fluent, do not have enthusiasm, and lack time deposits.